138k views
1 vote
Super confused definitely need help on this

Super confused definitely need help on this-example-1
User VietHTran
by
5.6k points

2 Answers

4 votes

Answer:

Explanation:

x^2 + 8x - 5x - 40

x^2 + 3x - 40

User Phil Huhn
by
4.9k points
4 votes

Answer:


(x-5)(x+8)=x^2+3x-40

Explanation:

So we have the expression:


(x-5)(x+8)

To multiply, distribute the left to the terms on the right:


=(x-5)(x)+(x-5)(8)

Distribute:


=(x^2-5x)+(8x-40)

Combine like terms:


=(x^2)+(-5x+8x)+(-40)

Simplify:


=x^2+3x-40

Therefore:


(x-5)(x+8)=x^2+3x-40

User Pravin Divraniya
by
5.5k points